2015
DOI: 10.1095/biolreprod.114.124115
|View full text |Cite
|
Sign up to set email alerts
|

IL10, TGF Beta1, and IFN Gamma Modulate Intracellular Signaling Pathways and Cytokine Production to Control Toxoplasma gondii Infection in BeWo Trophoblast Cells1

Abstract: Considering that interleukin 10 (IL10), transforming growth factor beta1 (TGFB1), and interferon gamma (IFNG) are involved in the susceptibility of BeWo trophoblast cells to Toxoplasma gondii infection, the aim of the present study was to investigate the effector mechanisms triggered by these cytokines in the control of T. gondii in BeWo cells. For this purpose, infected/uninfected BeWo cells were treated with IL10, TGFB1 (50 ng/ml), and IFNG (20 or 100 ng/ml) in order to verify the phosphorylation of signal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
1
19

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 80 publications
3
55
1
19
Order By: Relevance
“…Furthermore, we previously showed that BeWo cells treated with MIF or IL-6 recombinant cytokines significantly reduced the T. gondii proliferation, evidencing the important role of these mediators in the control of infection during a pregnancy (Barbosa et al, 2014, 2015). Then, the upregulation of these cytokines can be a mechanism triggered by the host cells, as trophoblast cells, to control the T. gondii infection.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Furthermore, we previously showed that BeWo cells treated with MIF or IL-6 recombinant cytokines significantly reduced the T. gondii proliferation, evidencing the important role of these mediators in the control of infection during a pregnancy (Barbosa et al, 2014, 2015). Then, the upregulation of these cytokines can be a mechanism triggered by the host cells, as trophoblast cells, to control the T. gondii infection.…”
Section: Introductionmentioning
confidence: 86%
“…In parallel, T. gondii tachyzoites from ME49 strain (moderate virulence) were provided from Dr. Karine Resende, Federal University of Triângulo Mineiro, MG, Brazil. Both parasite strains were maintained in culture flasks containing BeWo cells in RPMI 1640 medium supplemented with penicillin, streptomycin and 2% FBS at 37°C and 5% CO 2 (Angeloni et al, 2013; Barbosa et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations